THE RESULTS OF A PEDAGOGICAL EXPERIMENT ON THE PRESENCE OF PROFESSIONAL COMPETENCIES AMONG STUDENTS OF PEDAGOGICAL UNIVERSITIES (American Journal of Interdisciplinary Research and Development, 2023)
In this article we are talking about a pedagogical experiment, using the questionnaire method, conducted by us in 3 pedagogical universities of Uzbekistan, in order to check the availability of professional competencies of 3rd - 4th year students of the direction: "Physics and Astronomy". The purpose, objectives of the pedagogical experiment and its conclusions are described.